2018
DOI: 10.1371/journal.pone.0201717
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific factors related to suicidal ideation among community-dwelling stroke survivors: The 2013 Korean Community Health Survey

Abstract: We assessed gender-specific factors associated with suicidal ideation among community-dwelling stroke survivors. In total, 4,322 stroke survivors who participated in the 2013 Korean Community Health Survey were included in the final analysis. Sociodemographic information, socio-family relationships, health behaviors, health status, and suicidal ideation were assessed using a standardized questionnaire. On fully adjusted analysis, suicidal ideation among males was more common in those who were widowed, rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…The sample size of the included studies ranged from 19 [67] to 104,876 [68]. Of the studies that reported the sex of the participants ( n = 32, 62.7%) [5, 21, 22, 3136, 3842, 44, 4649, 5254, 5760, 65, 67, 68, 70, 71], 23 (71.8%) [5, 3133, 35, 38, 4042, 44, 4649, 55, 57, 58, 60, 65, 67, 68, 70, 71] used a male-dominated sample. In the 23 studies (45%) that provided information on age [5, 21, 22, 3234, 36, 38, 39, 41, 42, 44, 46, 48, 52, 55, 5760, 65, 67, 68], the mean age of the participants ranged from 43 ± 14 [45] to 77 ± 7 years [54].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size of the included studies ranged from 19 [67] to 104,876 [68]. Of the studies that reported the sex of the participants ( n = 32, 62.7%) [5, 21, 22, 3136, 3842, 44, 4649, 5254, 5760, 65, 67, 68, 70, 71], 23 (71.8%) [5, 3133, 35, 38, 4042, 44, 4649, 55, 57, 58, 60, 65, 67, 68, 70, 71] used a male-dominated sample. In the 23 studies (45%) that provided information on age [5, 21, 22, 3234, 36, 38, 39, 41, 42, 44, 46, 48, 52, 55, 5760, 65, 67, 68], the mean age of the participants ranged from 43 ± 14 [45] to 77 ± 7 years [54].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the SRH assessment, 72.5% of the studies ( n = 37) [5, 21, 22, 30, 33, 37, 39, 4346, 4952, 5964, 66, 6871, 7377] used general direct questions ( n = 21, 67.7%) [5, 30, 33, 37, 39, 43, 46, 49, 51, 5961, 64, 6871, 73, 74, 76, 77] or comparative direct questions ( n = 15, 48.4%) [5, 21, 22, 30, 44, 45, 50–52, 62, 63, 66, 69, 73, 75]. Comparative SRH referred to patients’ current health status in comparison to an earlier period [5, 37, 43, 51, 5456, 66] or to people of the same age [21, 22, 38, 43, 50, 56, 66, 69, 73, 75].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high incidence of adolescent suicide is believed to be precipitated by the myriad societal stressors experienced by young people (Turner et al, 2002). To illustrate: the following variables have been associated with suicide among adolescents: (a) substance use and/or abuse (e.g., Beautrais, 2000;Brennan and McGilloway, 2012); (b) affective mood disorders (e.g., Beautrais, 2000;Balázs et al, 2013;(c) antisocial behavior (e.g., Beautrais, 2000;Linker et al, 2012); (d) lower self-esteem (e.g., Overholser et al, 1995;Garber et al, 1997); (e) medical illnesses such as stroke and chronic illness (e.g., Ferro et al, 2017;Kim and Lee, 2018), and (f) depression (Lee et al, 2006). Other factors that have been associated with adolescent suicide include gender identity (e.g., Skagerberg et al, 2013;Yadegarfard et al, 2014), sexual orientation (e.g., Beautrais, 2000;Baams et al, 2015) and socioeconomic disadvantage (Yildiz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Strokes are considered one of the most debilitating neurological disorders, leading to physical impairment, disability, and death . Poststroke patients may also experience mental illnesses, such as depression, which is also linked to increased suicide risk …”
Section: Introductionmentioning
confidence: 99%